2008
DOI: 10.1128/aem.02304-07
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Correlation Spectroscopy To Study Diffusion and Reaction of Bacteriophages inside Biofilms

Abstract: In the natural environment, most of the phages that target bacteria are thought to exist in biofilm ecosystems. The purpose of this study was to gain a clearer understanding of the reactivity of these viral particles when they come into contact with bacteria embedded in biofilms. Experimentally, we quantified lactococcal c2 phage diffusion and reaction through model biofilms using in situ fluorescence correlation spectroscopy with two-photon excitation. Correlation curves for fluorescently labeled c2 phage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 58 publications
(64 reference statements)
6
92
0
1
Order By: Relevance
“…(19) suggested that although lytic phages showed considerable inhibitory effects on growth and biofilm formation in Pseudomonas aeruginosa, their effect on mature biofilms was very limited. While that may be due to extracellular polymeric substances (EPS) preventing phage access to the bacteria and/or the receptors for phage infection, there are other reports indicating that EPS has no obvious inhibitory effect on phage invasion (2). Engineering bacteriophage to express a biofilm-degrading enzyme during infection is one possible solution, and there are precedents.…”
Section: Discussionmentioning
confidence: 99%
“…(19) suggested that although lytic phages showed considerable inhibitory effects on growth and biofilm formation in Pseudomonas aeruginosa, their effect on mature biofilms was very limited. While that may be due to extracellular polymeric substances (EPS) preventing phage access to the bacteria and/or the receptors for phage infection, there are other reports indicating that EPS has no obvious inhibitory effect on phage invasion (2). Engineering bacteriophage to express a biofilm-degrading enzyme during infection is one possible solution, and there are precedents.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may involve multiple mechanisms, including interspecies signaling, spatial distribution of physiologically different bacteria, and interference from the matrix (3). Similarly, the low efficacy of phages to infect dual-species biofilms might be due to the protection of the sensitive host by the nonsensitive species (33,34), coaggregation of biofilm communities (35), limited penetration of phages (36,37), or changes in the availability of phage receptors on the cell surface of the host species (38). Despite the low efficacy from applying short phage treatments to dual-species cultures, microscopy revealed changes in the structures of treated biofilms compared with those of their respective controls.…”
Section: Discussionmentioning
confidence: 99%
“…57 Some studies have suggested that phages and bacteria can co-exist stably within a biofilm, [64][65][66] although presumably would not display the same phage-host dynamics observed for planktonic bacteria. For example, using fluorescence correlation spectroscopy to study diffusion and reaction of phages inside biofilms, Briandet et al 67 demonstrated that phages could diffuse within the biofilm, could be immobilized, amplified and released by a lytic cycle in the biofilm and could interact with their specific binding sites on the bacteria, even in the absence of lytic activity.…”
Section: Phage-host Dynamics In the Intestine: Ecological Assumptionsmentioning
confidence: 99%